VALORIZATION OF THE QUALITY OF THE PRODUCTS MADE BY ENTERPRISES ON THE MARKET WHERE THEY DO BUSINESS - Miletic, Vuk; Ćurčić, Nikola (Poslovna ekonomija, 2022)
The need of different enterprises for exploring the level of the quality of their products/services is growing with the expansion of their business operations in the global environment and with the growth of their competition. The subject matter of this research study is the valorization of certain characteristics of the products with which enterprises appear on a target market, which on their part especially relate to their quality. The purpose of the exploration and valorization of the product quality level is connected with numerous business arrangements of the enterprises competing in selected markets in a particular period of time so as to achieve an expected financial result. The starting premise implies that the installed concept of the quality of a product made by an enterprise should encompass all those quality elements pertaining to the consumer/user, i.e. to achieving their satisfaction. That is even more so given the fact that all the relevant analyses and experiences of global enterprises indicate that buyer/consumer satisfaction with a quality product ultimately decides on their financial success. In the research study, the comparative statistics, hypothetical-deductive, analytical-deductive and comparative, historical and statistical-descriptive methods are used.
Keywords: enterprise, quality valorization, product, competitiveness, business results